Hippocampus and Insula Are Targets in Epileptic Patients With Glutamic Acid Decarboxylase Antibodies - Falip, Mercè; Rodriguez-Bel, Laura; Castañer, Sara; Sala-Padró, Jacint; Miro, Júlia; Jaraba, Sónia; Casasnovas, Carlos; Morandeira, Francisco; Berdejo, Javier; Carreño, Mar (Frontiers in Neurology, 2019)
Background: Antibodies to glutamic acid decarboxylase (GAD ab) have been found in patients with limbic encephalitis (LE) and chronic pharmacoresistant focal epilepsy (FE). The objectives of the study were to: (1) analyze the clinical and neuroimaging course of patients with FE+GAD ab, (2) compare these characteristics with a control group, and (3) describe the most affected cerebral areas with structural and functional imaging. Methods: Patients with FE + high titers of GAD ab and a follow-up of at least 5 years were selected. Titers of serum GAD ab exceeding 2,000 UI/ml were considered high. Evolutive clinical and radiological characteristics were studied in comparison to two different control groups: patients with bilateral or with unilateral mesial temporal sclerosis (BMTS or UMTS) of a non-autoimmune origin. Results: A group of 13 patients and 17 controls were included (8 BMTS, 9 UMTS). The most frequent focal aware seizures (FAS) reported by patients were psychic (5/13: 33%). Somatosensorial, motor, and visual FAS (4/13:32%) (p: 0.045), musicogenic reflex seizures (MRS), and a previous history of cardiac syncope were reported only patients (2/13:16% each) (p: NS). Comparing EEG characteristics between patients and controls, a more widespread distribution of interictal epileptiform discharges (IED) was observed in FE+ GAD ab patients than in controls (p:0.01). Rhythmic delta activity was observed in all controls in anterior temporal lobes while in patients this was less frequent (p: 0.001). No IED, even in 24 h cVEEG, was seen in 6 patients (46%).First MRI was normal in 4/5 (75%) patients. During the follow-up mesial temporal lobe (MTsL) sclerosis was observed in 5/8 (62%) of patients. All patients had abnormal FDG-PET study. MTL hypometabolism was observed in 10/11 (91%) patients, being bilateral in 7/11 (63%). In controls, this was observed in 16/17 (94%), and it was bilateral in 8/17 (47%) (p: NS). Insular hypometabolism was observed in 5/11 (45%) patients (P:0.002). Conclusions: Clinical, EEG, and FDG-PET findings in FE+GAD ab suggest a widespread disease not restricted to the temporal lobe. Progressive MTL sclerosis may be observed during follow-up. In comparison to what is found in patients with non-autoimmune MTL epilepsy, insular hypometabolism is observed only in patients with GAD ab, so it may be an important diagnostic clue.